Telecoupling visualizations through a network lens: a systematic review - Gabi Sonderegger; Christoph Oberlack; Jorge C. Llopis; Peter H. Verburg; Andreas Heinimann (Ecology and Society, 2020)
Telecoupling is an integrative social-ecological framework that has made important contributions to understanding land change processes in a hyperconnected world. Visualizations are a powerful tool to communicate knowledge about telecoupling phenomena. However, little is known about current practices of telecoupling visualization and the challenges involved in visually displaying connections between multiple social-ecological systems. Our research takes stock of existing telecoupling visualizations and provides recommendations for improving current practices. We systematically review 118 visualizations presented in the scientific literature on telecoupling, and assess them in terms of their content and the adopted visualization approaches. To this end, we conceptualize telecoupling visualizations through a network lens. We find that they typically present networks of social-ecological systems, which are linked through flows. Displays of telecoupling connections through actor networks or action situation networks are less frequent. We categorize the existing visualizations into seven main types, which differ in terms of the visual encoding strategies used to represent telecoupling components. We then draw on insights from data visualization literature to reflect critically upon these current practices and provide practical recommendations. Finally, we show that network perspectives are inherent in telecoupling research and visualizations, and may deserve further attention in this field.